Effects and Safety of Allogenic Mesenchymal Stem Cell Intravenous Infusion in Active Ankylosing Spondylitis Patients who Failed NSAIDs: A 20-Week Clinical Trial. Issue 10 (October 2014) - Wang, Peng; Li, Yuxi; Huang, Lin; Yang, Jiewen; Yang, Rui; Deng, Wen; Liang, Biling; Dai, Lie; Meng, Qingqi; Gao, Liangbin; Chen, Xiaodong; Shen, Jun; et al.
Our objective was to evaluate the feasibility, safety, and efficacy of intravenous (IV) infusion of allogenic mesenchymal stem cells (MSCs) in ankylosing spondylitis (AS) patients who are refractory to or cannot tolerate the side effects of nonsteroidal anti-inflammatory drugs (NSAIDs). AS patients enrolled in this study received four IV infusions of MSCs on days 0, 7, 14, and 21. The percentage of ASAS20 responders (the primary endpoint) at the fourth week and the mean ASAS20 response duration (the secondary endpoint) were used to assess treatment response to MSC infusion and duration of the therapeutic effects. Ankylosing Spondylitis Disease Activity Score Containing C-reactive Protein (ASDAS-CRP) and other preestablished evaluation indices were also adopted to evaluate the clinical effects. Magnetic resonance imaging (MRI) was performed to detect changes of bone marrow edema in the spine. The safety of this treatment was also evaluated. Thirty-one patients were included, and the percentage of ASAS20 responders reached 77.4% at the fourth week, and the mean ASAS20 response duration was 7.1 weeks. The mean ASDAS-CRP score decreased from 3.6 ± 0.6 to 2.4 ± 0.5 at the fourth week and then increased to 3.2 ± 0.8 at the 20th week. The average total inflammation extent (TIE) detected by MRI decreased from 533, 482.5 at baseline to 480, 692.3 at the fourth week ( p > 0.05) and 400, 547.2 at the 20th week ( p < 0.05). No adverse effects were noted. IV infusion of MSCs is a feasible, safe, and promising treatment for patients with AS.